In vitro Studies on Pollen Viability, Pollen Germination and Pollen Tube Growth of Hornstedtia conoidea Ridl. – a Philippine Endemic Ginger Species - Mendez, Noe Polo; Acma, Florfe Macabudbud (Journal of Tropical Life Science, 2018)
Zingiberaceous plants are predominantly propagated through underground rhizomes and seeds. In this study, the viability of pollen, rate of pollen germination and length of pollen tube of the Philippine endemic Hornstedtia conoidea were examined. Four petri plates containing pollen samples were prepared, of which two petri plates were used immediately after the collection, while the other two petri plates were stored for one week. The determination of pollen viability was made employing stain tests using IKI (iodine + potassium iodide) solution and safranin and measured immediately after the collection and after one week. Likewise, pollen germination test was carried out in vitro on agar medium and measured after 24 hours and one week of incubation. Data revealed that pollen viability was higher in the samples which were sown immediately with safranin with percentage pollen viability of 92.43%, while IKI test was lower with 89.36%. On the other hand, the pollen stored for one week measured 47.29% for safranin test and 33.14% for IKI test. The percentage germination of pollen after 24 hours was 72.65%, while 11.13% after one week. The pollen samples which were subjected for tube growth were examined for two weeks and gave positive results. Overall, it can be concluded that H. conoidea pollen can successfully be collected and stored for certain time. Knowledge regarding the pollen viability, pollen germination and pollen tube growth of this species will give practical benefit for plant breeding and conservation purposes, since H. conoidea is found in the wild, and as of now, the species has been recorded only in the Philippines.